GARNET REEQUILIBRATION AND GROWTH IN THE ECLOGITE FACIES AND GEODYNAMICAL EVOLUTION NEAR PEAK METAMORPHIC CONDITIONS - Raimbourg H.; Goffé B.; Jolivet L. (My University, 2007)
Caledonian eclogite-facies metamorphism partially reworking Grenvillian granulite-facies anorthosite allows us to study the processes of garnet reequilibration at high pressure and to reconstruct the evolution of the unit near metamorphic peak conditions. Our results indicate that eclogite-facies metamorphism happened in two successive phases: first, inherited granulitic garnet was fractured and reequilibrated from their boundaries (crystal or fracture rims); then eclogite-facies minerals were crystallised in the fractures as overgrowths on inherited garnets. The reequilibration of inherited garnets is achieved through Fe2+Mg-1 exchange, whereas eclogite-facies garnets crystallised during the subsequent phase are notably richer in Ca than un- and re-equilibrated granulitic garnet. Pseudosection construction shows that this lack in Ca reequilibration cannot be related to variations in thermodynamic conditions (aH20, reacting system composition) between the two phases. From the compilation of the available data, the reequilibration of granulitic garnet seems to be controlled by the inefficient intra- and inter-granular transport properties of Ca compared to Fe2+ and Mg. While these kinetic factors confine garnet reequilibration to Fe2+Mg-1 exchange, the extent of reequilibration along this exchange vector is controlled by partitioning with adjacent omphacite. On the contrary to the diffusional reequilibration of granulitic garnet that lasted for several My according to our modelling of the diffusional relaxation, the strong compositional gradients between eclogite-facies and reequilibrated garnets, which are almost unaffected by diffusional reequilibration, provide evidence that rapid exhumation followed the crystallisation of eclogite-facies minerals. We propose that the movement reversal itself, from burial to exhumation, and associated deformation and fluid flow, triggered this crystallisation event. The resulting evolution near metamorphic peak conditions is therefore strongly asymmetrical: on the one hand, the prograde diffusional relaxation profiles indicate slow movement during the last stages of burial, whereas the unaffected retrograde overgrowth indicates fast exhumation rates. © Springer-Verlag 2006.